PENERAPAN USER-CENTERED DESIGN DALAM REDESAIN WEBSITE PPID KOTA DENPASAR: STUDI EVALUASI DENGAN SYSTEM USABILITY SCALE (SUS) - Ni Nyoman Sukma Prasetyadewi Gita; I Made Widhi Wirawan; I Dewa Made Bayu Atmaja Darmawan (Jurnal Pengabdian Informatika, 2026)
The PPID Denpasar City website serves as an essential platform for public information transparency, but its previous design did not effectively meet user needs. This study applies the User-Centered Design (UCD) method through four stages: understanding the context of use, specifying user requirements, producing design solutions, and evaluating the design. Using this approach, a more modern and responsive redesign was developed to align with user expectations. The redesign resulted in significant improvements in visual appearance, functionality, navigation, and information accessibility. An evaluation using the System Usability Scale (SUS) produced an average score of 77.92, which falls into the “Good” category, indicating a high level of usability. This research demonstrates that the UCD approach is effective in enhancing user satisfaction and supports the principles of public information transparency.